Teacher Development and Management at Secondary Education in Nepal - Shrestha, Kedar N (Journal of Education and Research, 2008)
Though the concept of teacher development was institutionalized in 1971, the policy of the government on this issue has not remained consistent. When the government started its own institutions to provide in-service training to teachers, the universities started losing the government support to improve their professional programs. As a result, the pre-service training programs gradually converted into academic and less professional program. ! ere are issues emerging in the effectiveness of the training and the concerns how to better shape the teacher education in Nepal. ! is paper discusses the context and recommend measures that can bring the teacher education to the right track. DOI: http://dx.doi.org/10.3126/jer.v1i0.7950 Journal of Education and Research 2008, Vol. 1, No. 1, pp. 41-50